Mucormycosis of stomach - Joshi, Gaurav; Singh, Devender; Rathore, Yashwant Singh; Singh, Bhanupratap (International Surgery Journal, 2019)
Gastrointestinal mucormycosis is invasive fungal infection with very high mortality if not treated. Early diagnosis is critical. We managed a case of mucormycosis of stomach which was a diagnostic challenge. As symptoms are not specific an upper gastrointestinal endoscopy plays the most important role in the diagnosis of mucormycosis of stomach. Upon endoscopy it may be confused with food material (bread) or a foreign body (Bezoars). Diagnosis is easily missed unless there is very high index of suspicion. Surgical resection of involved organ in combination with systemic administration of amphoterecin B is treatment of choice.